A highly flexible and resistant robot cable

By using multi-component material formulation and modified carbon fiber technology in the outer sheath layer of the robot cable, the problem of existing cables being prone to break during high frequency movement is solved, and the excellent performance of high flexibility and winding resistance is achieved, which extends the service life of the cable.

CN119108134BActive Publication Date: 2025-03-25HANGZHOU LINAN GUANGDA CABLE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411595211.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-25
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

Existing robotic cables are prone to permanent deformation or breaking during high frequency movement, and the material is difficult to meet high flexibility and excellent winding resistance at the same time.

Method used

A new outer sheath layer material formula is adopted, including PVC resin, nitrile rubber powder, polyolefin thermoplastic elastomer, trioctyl trimelite, dioctyl sebate, aluminum hydroxide, carbon black, modified carbon fiber, thermal stabilizer, antioxidant and lubricant. The comprehensive performance of the material is improved through carefully designed component ratios and the preparation method of modified carbon fiber.

Benefits of technology

It achieves high flexibility, excellent winding resistance, good oil and chemical resistance, as well as excellent mechanical strength and wear resistance, extends the service life of the cable and reduces maintenance and replacement costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119108134B_ABST
    Figure CN119108134B_ABST
Patent Text Reader

Abstract

The invention discloses a high-flexibility and bending-resistant robot cable, and relates to the technical field of robot cables. The robot cable comprises a plurality of cable cores, which are coated by a tape layer, wherein a filler is filled in a twisted gap of the cable core, the tape layer is coated with a shielding layer, and the shielding layer is coated with an outer sheath layer; the outer sheath layer is made of the following components: 80-100 parts of PVC resin, 30-60 parts of nitrile rubber powder, 20-30 parts of polyolefin thermoplastic elastomer, 10-30 parts of trioctyl trimellitate, 5-15 parts of dioctyl sebacate, 5-25 parts of aluminum hydroxide, 8-15 parts of carbon black, 10-20 parts of modified carbon fiber, 3-6 parts of a heat stabilizer, 1-3 parts of an antioxidant, and 1-3 parts of a lubricant; the invention realizes an optimized balance among flexibility, bending resistance, mechanical strength and environmental adaptability, and provides a high-performance and long-life key component for modern industrial automation and robot applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of robot cables, and in particular to a highly flexible and bend-resistant robot cable. Background Art

[0002] With the rapid development of industrial automation and intelligent manufacturing, industrial robots are increasingly used in various fields. As a key component of robots, robot cables assume the important function of transmitting power and signals. This special cable is not only used in traditional industrial manufacturing fields such as automobile assembly and electronic product production lines, but also widely used in emerging high-end fields such as intelligent warehousing, medical surgical robots and precision instrument manufacturing.

[0003] Robot cables need to maintain stable and reliable performance during high-speed and high-frequency movements, which places extremely high demands on their flexibility, bending resistance, and electrical performance. However, traditional robot cables face many challenges during long-term use. Existing cable outer sheath materials often have difficulty maintaining strength while providing sufficient flexibility, causing the cable to easily undergo permanent deformation or breakage during high-frequency movements. Due to the movement characteristics of robots, cables need to withstand repeated bending and torsion. Under such conditions, existing materials are prone to damage to the internal structure of the cable, especially conductor breakage and cracking of the insulation layer.

[0004] At present, the outer sheath of robot cables on the market mainly adopts materials such as polyvinyl chloride (PVC), polyurethane (PU) or polyethylene (PE). These materials are difficult to meet the requirements of high flexibility and excellent bending resistance at the same time. For example, PVC material has certain strength but insufficient flexibility; PU material has good flexibility but poor heat resistance; PE material has good electrical insulation performance, but its flexibility still needs to be improved. The performance of these single materials may be significantly reduced in complex working environments, increasing the risk of cable damage.

[0005] CN117467203A discloses a tear-resistant and wear-resistant cable sheath material, whose raw materials and weight percentages are as follows: 40-50 parts of nitrile rubber, 30-40 parts of modified PVC resin, 1-3 parts of plasticizer, 3-5 parts of antioxidant, 1-3 parts of flame retardant, 7-9 parts of carbon black, 5-10 parts of zinc oxide, 3-5 parts of sulfur, 3-5 parts of stabilizer, 10-14 parts of filler, 0.5-1.5 parts of magnesium oxide, and 4-6 parts of stearic acid.

[0006] In the outer sheath material formula proposed in the prior art, the addition of certain components may affect the overall performance balance of the material, making it difficult to achieve high flexibility and excellent bending resistance at the same time. These problems seriously restrict the performance and service life of the robot.

[0007] Therefore, there is an urgent need to develop a new type of highly flexible and resistant robot cable, whose outer sheath material formula can effectively balance various performance indicators, especially achieve breakthroughs in flexibility and flexural resistance, meet the growing performance requirements of modern industrial robots, extend service life, and thus improve the overall performance and reliability of the robot. Summary of the invention

[0008] In order to address the deficiencies in the prior art, the purpose of the present invention is to provide a highly flexible and resistant to bending robot cable, which achieves an optimized balance of flexibility, bending resistance, mechanical strength and environmental adaptability through innovative material formulation and structural design, providing a high-performance, long-life key component for modern industrial automation and robotic applications.

[0009] In order to achieve the above object, the present invention adopts the following technical solution:

[0010] A highly flexible and bend-resistant robot cable comprises a plurality of cable cores, wherein the plurality of cable cores are coated by a tape layer, a filler is filled in a twisted gap of the cable core, a shielding layer is coated outside the tape layer, and an outer sheath layer is coated outside the shielding layer; the outer sheath layer is made of the following components in parts by weight: 80-100 parts of PVC resin, 30-60 parts of nitrile rubber powder, 20-30 parts of polyolefin thermoplastic elastomer, 10-30 parts of trioctyl trimellitate, 5-15 parts of dioctyl sebacate, 5-25 parts of aluminum hydroxide, 8-15 parts of carbon black, 10-20 parts of modified carbon fiber, 3-6 parts of heat stabilizer, 1-3 parts of antioxidant, and 1-3 parts of lubricant.

[0011] Preferably, the filler is one or more of polyester yarn, aramid yarn, and cotton thread.

[0012] Preferably, the heat stabilizer is one or more of a calcium zinc heat stabilizer, an organic tin heat stabilizer, and a rare earth heat stabilizer.

[0013] Preferably, the antioxidant is one or more of hindered phenols, phosphates, and sulfur-containing auxiliary antioxidants.

[0014] Preferably, the lubricant is one or more of paraffin wax, PE wax, microcrystalline wax, and stearic acid.

[0015] Preferably, the method for preparing the modified carbon fiber comprises the following steps:

[0016] (1) Immersing the carbon fiber in an ethanol / water mixture, adding KH570, adjusting the pH of the solution, stirring at room temperature, heating the solution for reaction, filtering, washing, and drying the product to obtain a pretreated carbon fiber;

[0017] KH570 pretreatment (silanization): In this step, KH570 (γ-methacryloxypropyltrimethoxysilane) reacts with the hydroxyl groups on the surface of the carbon fiber. First, KH570 is hydrolyzed under acidic conditions to generate silanol groups. Then, these silanol groups undergo condensation reaction with the hydroxyl groups on the surface of the carbon fiber to form Si-OC bonds while releasing water molecules. This process forms a layer of organic silane containing double bonds on the surface of the carbon fiber, which increases the surface activity and reactivity of the carbon fiber. Reaction mechanism: R-Si(OCH3)3+3H2O→R-Si(OH)3+3CH3OH; R-Si(OH)3+Fiber-OH→R-Si(OH)2-O-Fiber+ H2O.

[0018] Preferably, in step (1), the carbon fiber is PAN-based carbon fiber T300, with a diameter of 6.91 μm and a length of 1 to 3 mm.

[0019] Preferably, in step (1), the volume ratio of ethanol to water in the ethanol / water mixture is 95-99:5-1; and the usage ratio of carbon fiber, ethanol / water mixture, and KH570 is 10 g: 200-300 mL: 0.1-1 g.

[0020] Preferably, in step (1), the pH is adjusted to 3.5-5.5, and the mixture is stirred at room temperature for 30-60 min. The temperature is raised to 60-80° C. for 2-4 h. The mixture is washed with 95 wt % ethanol solution for 3-5 times, each time for 15-20 min.

[0021] (2) adding the pretreated carbon fiber into anhydrous toluene, slowly adding dimethylchlorosilane and Speier's catalyst solution under a nitrogen atmosphere, stirring at room temperature, heating to reflux for reaction, filtering, washing, and drying the product to obtain an intermediate;

[0022] Dimethylchlorosilane grafting (hydrogen silylation): The pretreated carbon fiber undergoes a hydrosilylation reaction with dimethylchlorosilane under the action of Speier's catalyst (H2PtCl6). The platinum catalyst promotes the addition reaction between the Si-H bond and the C=C double bond introduced by KH570 to form a Si-C bond. This step introduces chlorosilane groups on the surface of the carbon fiber, providing active sites for subsequent reactions. Reaction mechanism: Fiber-O-Si-CH2-CH2-CH2-OC(O)-C(CH3)=CH2+(CH3)2SiHCl→Fiber-O-Si-CH2-CH2-CH2-OC(O)-CH(CH3)-CH2-Si(CH3)2Cl.

[0023] Preferably, in step (2), the Speier's catalyst solution is a 2wt% H2PtCl6 isopropanol solution; the dosage ratio of the pretreated carbon fiber, anhydrous toluene, dimethylchlorosilane, and Speier's catalyst solution is 10g: 200~300mL: 5~10mL: 0.1~0.5mL.

[0024] Preferably, in step (2), stirring is performed at room temperature for 30 to 60 minutes, and the reflux reaction conditions are heating to 60 to 80°C and reflux reaction for 4 to 8 hours; washing with dry toluene 3 to 5 times, each time for 15 to 20 minutes; and vacuum drying at 40 to 60°C for 4 to 6 hours.

[0025] (3) The intermediate is added to anhydrous tetrahydrofuran, and 5-amino-2-fluorobenzoate and triethylamine are slowly added under a nitrogen atmosphere. The mixture is mixed evenly at low temperature, and the reaction is stirred. The product is filtered, washed, and dried to obtain modified carbon fibers.

[0026] 5-amino-2-fluorobenzoate modification: The last step is to graft 5-amino-2-fluorobenzoate onto the carbon fiber surface. The amino group undergoes a nucleophilic substitution reaction with the chlorosilane group introduced in the previous step, and releases HCl (neutralized by triethylamine) under the action of triethylamine. This step introduces functional groups containing terminal methyl esters, benzene rings, and fluorine on the surface of the carbon fiber, further changing the surface properties of the carbon fiber and enhancing its compatibility with specific matrix materials and interfacial bonding strength. Reaction mechanism: Fiber-Si(CH3)2Cl+H2N-C6H4-COOEt+Et3N→Fiber-Si(CH3)2-NH-C6H4-COOEt + Et3N·HCl.

[0027] Preferably, in step (3), the ratio of the intermediate, anhydrous tetrahydrofuran, 5-amino-2-fluorobenzoate solution, and triethylamine is 10 g: 200-300 mL: 2-5 g: 0.5-3 mL.

[0028] Preferably, in step (3), the low-temperature mixing condition is stirring at 0-5°C for 30-60 minutes; and the stirring reaction condition is reacting at room temperature for 6-12 hours.

[0029] Preferably, in step (3), the product is washed with 0.1 mol / L sodium bicarbonate solution for 3 times, washed with deionized water for 3 to 5 times, and washed with anhydrous ethanol for 2 times, each time for 15 to 20 minutes; and vacuum dried at 60 to 80°C for 8 to 12 hours.

[0030] Preferably, the preparation method of the outer sheath comprises the following steps: mixing the raw materials uniformly at a high speed at 70-90°C according to a ratio, wherein the modified carbon fiber is added in equal amounts three times during the stirring process, adding the mixture into an internal mixer, and mixing at 160-175°C for 8-12 minutes to obtain a clinker, placing it in a twin-screw extruder, and extruding and granulating it at 180-200°C to obtain a masterbatch, and extruding the wire through the screw extruder to obtain the outer sheath.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The present invention provides a highly flexible and resistant bending robot cable, which achieves excellent comprehensive performance through a carefully designed outer sheath material formula. PVC resin, as a basic material, provides good processing performance and basic mechanical strength. The addition of nitrile rubber powder significantly improves the flexibility and oil resistance of the cable, allowing the cable to maintain good performance in frequent bending and complex environments. Polyolefin thermoplastic elastomers further enhance the elasticity and fatigue resistance of the material and improve the bending life of the cable. Trioctyl trimellitate and dioctyl sebacate are used as plasticizers to improve the flexibility and low temperature performance of PVC while maintaining the heat resistance of the material. The addition of aluminum hydroxide improves the flame retardancy and enhances the safety performance of the cable. Carbon black not only plays a coloring role, but also improves the UV resistance and conductivity of the material. The addition of modified carbon fiber is a major innovation of the present invention, which significantly improves the mechanical strength, wear resistance and tensile strength of the outer sheath, while improving the conductivity and antistatic properties. The reasonable ratio of heat stabilizers, antioxidants and lubricants ensures the stability and durability of the material during processing and use. The synergistic effect of this multi-component formula gives the outer sheath excellent comprehensive properties, including high flexibility, excellent bending resistance, good oil resistance and chemical resistance, as well as excellent mechanical strength and wear resistance. Combined with the cable's structural design, such as the use of cable core gap fillers and the setting of the shielding layer, the cable's compression resistance, flexibility and anti-electromagnetic interference ability are further enhanced. These characteristics make the cable particularly suitable for robots and other automation equipment that require frequent bending and movement. It can maintain stable signal transmission and long-term reliable performance in complex industrial environments, greatly extending the service life of the cable and reducing maintenance and replacement costs.

[0033] 2. The present invention provides a method for preparing modified carbon fiber. First, KH570 (γ-methacryloxypropyltrimethoxysilane) is used to pre-treat the carbon fiber by silanization. After the methoxy group in KH570 is hydrolyzed, it undergoes a condensation reaction with the hydroxyl group on the surface of the carbon fiber to form a Si-OC bond, and an organic silane layer containing a C=C double bond is introduced on the surface of the carbon fiber. This step increases the surface activity and reactivity of the carbon fiber, laying the foundation for subsequent modification. Then, dimethylchlorosilane is grafted onto the surface of the pretreated carbon fiber through a hydrosilation reaction assisted by Speier's catalyst. In this step, the Si-H bond in dimethylchlorosilane reacts with the C=C double bond introduced in the previous step to form a Si-C bond. This process introduces chlorinated silane groups on the surface of the carbon fiber, providing active sites for the last step of the reaction. Finally, 5-amino-2-fluorobenzoate is reacted with the intermediate to introduce fluorinated benzoate groups on the surface of the carbon fiber. The amino group in 5-amino-2-fluorobenzoate undergoes a nucleophilic substitution reaction with the chlorosilane group introduced in the previous step, forming a Si-N bond on the carbon fiber surface, while introducing a fluorinated benzene ring and an ester structure. This multi-step, multifunctional group introduction strategy gives the modified carbon fiber unique surface properties, which can significantly improve its performance in composite materials.

[0034] 3. The present invention provides a modified carbon fiber. First, the long-chain alkyl introduced by KH570 as a flexible segment significantly increases the interfacial compatibility between the carbon fiber and the resin matrix, and improves the toughness and impact resistance of the composite material. The long-chain structure can also form a physical entanglement between the carbon fiber and the matrix, further enhancing the interfacial bonding strength. The reactive double bonds introduced at the same time provide important chemical reaction sites for subsequent modification. Secondly, the silane group introduced by dimethylchlorosilane grafting forms a flexible transition layer between the carbon fiber and the resin matrix, effectively alleviating the interfacial stress concentration and improving the overall toughness and fatigue resistance of the composite material. The presence of the silane group also improves the heat resistance and dimensional stability of the composite material, and enhances the application performance of the material under high temperature environment. Finally, the introduction of 5-amino-2-fluorobenzoate brings multiple benefits. The benzene ring as a rigid functional group significantly improves the mechanical strength, thermal stability and tensile strength of the resin matrix. The terminal methyl ester structure as a plasticizing functional group increases the compatibility with PVC, and enhances the interfacial bonding force by forming hydrogen bonds and other interactions with the PVC molecular chain, while improving the processing performance and surface quality of the composite material. The introduced fluorine atoms greatly improve the hydrophobicity, chemical resistance and weather resistance of the material, making the composite material more waterproof, oil-proof and corrosion-resistant, while also improving the demoulding performance and surface finish. The synergistic effect of this multifunctional group enables the modified carbon fiber to exhibit excellent comprehensive performance in the composite material. The modified carbon fiber has better dispersibility and compatibility with the polymer matrix, effectively improving the distribution of carbon fiber in the outer sheath material and the interfacial bonding strength. These modification effects together lead to a significant improvement in the mechanical strength, wear resistance, flexibility and chemical resistance of the outer sheath material. In addition, the modified carbon fiber also helps to improve the electrical conductivity and antistatic properties of the cable, while improving the heat resistance and dimensional stability of the cable. These excellent properties make the modified carbon fiber a key component for improving the performance of high-flexibility and resistant bending robot cables, providing high-performance and long-life key material support for modern industrial automation and robotic applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show schematic diagrams of certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 A schematic diagram of the highly flexible and bend-resistant robot cable provided by the present invention.

[0037] In the figure, 1, cable core; 2, tape layer; 3, filler; 4, shielding layer; 5, outer sheath layer. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0039] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.

[0040] The degree of polymerization of PVC resin is 800~2500, such as SG-3 type resin;

[0041] The nitrile rubber powder is P83 nitrile rubber;

[0042] The polyolefin thermoplastic elastomer is Korean LG POE LC170;

[0043] The carbon black has an iodine absorption value of 82±7 g / kg and a DBP absorption value of 102±7 (10 -5 m 3 / kg), the CTAB adsorption specific surface area is 76~88(10 3 m 2 / kg), 45μm sieve residue ≤0.10%, average particle size of N330 reinforcing carbon black 27~34nm.

[0044] The carbon fiber was pretreated before use, placed at 60°C and dried for 30 minutes; immersed in 1 mol / L hydrochloric acid solution for 2 hours, taken out, washed with water, and dried.

[0045] like Figure 1 As shown, the present invention provides a highly flexible and bend-resistant robot cable, comprising a plurality of cable cores 1, wherein the plurality of cable cores 1 are coated with a tape layer 2, wherein the twisted gaps of the cable cores 1 are filled with a filler 3, the tape layer 2 is coated with a shielding layer 4, and the shielding layer 4 is coated with an outer sheath layer 5.

[0046] A method for preparing a highly flexible and resistant robot cable outer sheath comprises the following steps:

[0047] (1) Immerse 10 g of carbon fiber in 200-300 mL of ethanol / water mixture (the volume ratio of ethanol to water is 95-99:5-1), add 0.1-1 g of KH570, adjust the pH of the solution to 3.5-5.5, stir at room temperature for 30-60 min, heat to 60-80 °C and react for 2-4 h, filter the product, wash it with 95 wt% ethanol solution for 3-5 times, each time for 15-20 min, and dry it to obtain pretreated carbon fiber;

[0048] (2) Add 10 g of pretreated carbon fiber to 200-300 mL of anhydrous toluene, slowly add 5-10 mL of dimethylchlorosilane and 0.1-0.5 mL of Speier's catalyst solution (2 wt% H2PtCl6 isopropanol solution) under nitrogen atmosphere, stir at room temperature for 30-60 min, heat to 60-80 °C and reflux for 4-8 h, filter the product, wash with dry toluene 3-5 times, each time for 15-20 min, and vacuum dry at 40-60 °C for 4-6 h to obtain an intermediate;

[0049] (3) Add 10 g of the intermediate to 200-300 mL of anhydrous tetrahydrofuran, slowly add 2-5 g of 5-amino-2-fluorobenzoate and 0.5-3 mL of triethylamine under a nitrogen atmosphere, stir at 0-5 ° C for 30-60 min, stir at room temperature for 6-12 h, filter the product, wash it 3 times with 0.1 mol / L sodium bicarbonate solution, wash it 3-5 times with deionized water, wash it 2 times with anhydrous ethanol, each time for 15-20 min, and vacuum dry it at 60-80 ° C for 8-12 h to obtain modified carbon fiber;

[0050] (4) Take 80-100 parts of PVC resin, 30-60 parts of nitrile rubber powder, 20-30 parts of polyolefin thermoplastic elastomer, 10-30 parts of trioctyl trimellitate, 5-15 parts of dioctyl sebacate, 5-25 parts of aluminum hydroxide, 8-15 parts of carbon black, 10-20 parts of modified carbon fiber, 3-6 parts of heat stabilizer, 1-3 parts of antioxidant, and 1-3 parts of lubricant, and mix them uniformly at 70-90°C at high speed, wherein the modified carbon fiber is added in equal amounts three times during the stirring process, and the mixture is added to an internal mixer, and internally kneaded at 160-175°C for 8-12 minutes to obtain a clinker, which is placed in a twin-screw extruder, extruded and granulated at 180-200°C to obtain a masterbatch, and extruded the wire through the screw extruder to obtain the outer sheath.

[0051] The present invention will be further described below through specific embodiments.

[0052] Example 1

[0053] A method for preparing a highly flexible and resistant robot cable outer sheath material comprises the following steps:

[0054] (1) Immerse 10 g of carbon fiber in 250 mL of ethanol / water mixture (volume ratio of ethanol to water is 95:5), add 1 g of KH570, adjust the solution pH to 4.5, stir at room temperature for 45 min, heat to 80 °C for reaction for 2 h, filter the product, wash it 4 times with 95 wt% ethanol solution, each time for 15 min, and dry it to obtain pretreated carbon fiber;

[0055] (2) Add 10 g of pretreated carbon fiber to 250 mL of anhydrous toluene, slowly add 10 mL of dimethylchlorosilane and 0.5 mL of Speier's catalyst solution (2 wt% H2PtCl6 isopropanol solution) under nitrogen atmosphere, stir at room temperature for 45 min, heat to 80 °C and reflux for 4 h, filter the product, wash with dry toluene 4 times, 15 min each time, and vacuum dry at 50 °C for 5 h to obtain an intermediate;

[0056] (3) Add 10 g of the intermediate to 250 mL of anhydrous tetrahydrofuran, slowly add 5 g of 5-amino-2-fluorobenzoate and 3 mL of triethylamine under a nitrogen atmosphere, stir at 5 ° C for 30 min, stir at room temperature for 12 h, filter the product, wash it 3 times with 0.1 mol / L sodium bicarbonate solution, wash it 4 times with deionized water, wash it 2 times with anhydrous ethanol, each time for 15 min, and vacuum dry it at 70 ° C for 10 h to obtain modified carbon fiber;

[0057] (4) Take 1000g of PVC resin, 600g of nitrile rubber powder, 300g of polyolefin thermoplastic elastomer, 300g of trioctyl trimellitate, 150g of dioctyl sebacate, 250g of aluminum hydroxide, 150g of carbon black, 200g of modified carbon fiber, 60g of heat stabilizer, 30g of antioxidant, and 30g of lubricant, and mix them evenly at 80°C with high-speed stirring, wherein the modified carbon fiber is added in equal amounts three times during the stirring process. The mixture is added to an internal mixer and kneaded at 165°C for 10 minutes to obtain a clinker, which is placed in a twin-screw extruder and extruded and granulated at 190°C to obtain a masterbatch, which is extruded through a screw extruder to obtain the outer sheath.

[0058] Example 2

[0059] A method for preparing a highly flexible and resistant robot cable outer sheath material comprises the following steps:

[0060] (1) Immerse 10 g of carbon fiber in 250 mL of ethanol / water mixture (volume ratio of ethanol to water is 95:5), add 0.7 g of KH570, adjust the solution pH to 4.5, stir at room temperature for 45 min, heat to 75 °C for reaction for 3 h, filter the product, wash it 4 times with 95 wt% ethanol solution, each time for 15 min, and dry it to obtain pretreated carbon fiber;

[0061] (2) Add 10 g of pretreated carbon fiber to 250 mL of anhydrous toluene, slowly add 8 mL of dimethylsilyl chloride and 0.4 mL of Speier's catalyst solution (2 wt% H2PtCl6 isopropanol solution) under nitrogen atmosphere, stir at room temperature for 45 min, heat to 75 °C and reflux for 6 h, filter the product, wash with dry toluene 4 times, 15 min each time, and vacuum dry at 50 °C for 5 h to obtain an intermediate;

[0062] (3) Add 10 g of the intermediate to 250 mL of anhydrous tetrahydrofuran, slowly add 4 g of 5-amino-2-fluorobenzoate and 2.5 mL of triethylamine under a nitrogen atmosphere, stir at 4 ° C for 50 min, stir at room temperature for 10 h, filter the product, wash it 3 times with 0.1 mol / L sodium bicarbonate solution, wash it 4 times with deionized water, wash it 2 times with anhydrous ethanol, each time for 15 min, and vacuum dry it at 70 ° C for 10 h to obtain modified carbon fiber;

[0063] (4) Take 900g of PVC resin, 500g of nitrile rubber powder, 270g of polyolefin thermoplastic elastomer, 240g of trioctyl trimellitate, 120g of dioctyl sebacate, 180g of aluminum hydroxide, 120g of carbon black, 170g of modified carbon fiber, 50g of heat stabilizer, 24g of antioxidant, and 24g of lubricant, and mix them evenly at 80°C with high-speed stirring, wherein the modified carbon fiber is added in equal amounts three times during the stirring process. The mixture is added to an internal mixer and kneaded at 165°C for 10 minutes to obtain a clinker, which is placed in a twin-screw extruder and extruded and granulated at 190°C to obtain a masterbatch, which is extruded through a screw extruder to obtain the outer sheath.

[0064] Example 3

[0065] A method for preparing a highly flexible and resistant robot cable outer sheath material comprises the following steps:

[0066] (1) Immerse 10 g of carbon fiber in 250 mL of ethanol / water mixture (volume ratio of ethanol to water is 95:5), add 0.4 g of KH570, adjust the solution pH to 4.5, stir at room temperature for 45 min, heat to 65 °C for reaction for 3 h, filter the product, wash it 4 times with 95 wt% ethanol solution, each time for 15 min, and dry it to obtain pretreated carbon fiber;

[0067] (2) Add 10 g of pretreated carbon fiber to 250 mL of anhydrous toluene, slowly add 6 mL of dimethylsilyl chloride and 0.2 mL of Speier's catalyst solution (2 wt% H2PtCl6 isopropanol solution) under nitrogen atmosphere, stir at room temperature for 45 min, heat to 65 °C and reflux for 6 h, filter the product, wash with dry toluene 4 times, 15 min each time, and vacuum dry at 50 °C for 5 h to obtain an intermediate;

[0068] (3) Add 10 g of the intermediate to 250 mL of anhydrous tetrahydrofuran, slowly add 3 g of 5-amino-2-fluorobenzoate and 1 mL of triethylamine under a nitrogen atmosphere, stir at 2 ° C for 40 min, stir at room temperature for 8 h, filter the product, wash it 3 times with 0.1 mol / L sodium bicarbonate solution, wash it 4 times with deionized water, wash it 2 times with anhydrous ethanol, each time for 15 min, and vacuum dry it at 70 ° C for 10 h to obtain modified carbon fiber;

[0069] (4) Take 900g of PVC resin, 400g of nitrile rubber powder, 240g of polyolefin thermoplastic elastomer, 160g of trioctyl trimellitate, 80g of dioctyl sebacate, 120g of aluminum hydroxide, 100g of carbon black, 140g of modified carbon fiber, 40g of heat stabilizer, 16g of antioxidant, and 16g of lubricant, and mix them evenly at 80°C with high-speed stirring, wherein the modified carbon fiber is added in equal amounts three times during the stirring process. The mixture is added to an internal mixer and kneaded at 165°C for 10 minutes to obtain a clinker, which is placed in a twin-screw extruder and extruded and granulated at 190°C to obtain a masterbatch, which is extruded through a screw extruder to obtain the outer sheath.

[0070] Example 4

[0071] A method for preparing a highly flexible and resistant robot cable outer sheath material comprises the following steps:

[0072] (1) Immerse 10 g of carbon fiber in 250 mL of ethanol / water mixture (volume ratio of ethanol to water is 95:5), add 0.1 g of KH570, adjust the solution pH to 4.5, stir at room temperature for 45 min, heat to 60 °C for 4 h, filter the product, wash it 4 times with 95 wt% ethanol solution, each time for 15 min, and dry it to obtain pretreated carbon fiber;

[0073] (2) Add 10 g of pretreated carbon fiber to 250 mL of anhydrous toluene, slowly add 5 mL of dimethylchlorosilane and 0.1 mL of Speier's catalyst solution (2 wt% H2PtCl6 isopropanol solution) under nitrogen atmosphere, stir at room temperature for 45 min, heat to 60 °C and reflux for 8 h, filter the product, wash with dry toluene 4 times, 15 min each time, and vacuum dry at 50 °C for 5 h to obtain an intermediate;

[0074] (3) Add 10 g of the intermediate to 250 mL of anhydrous tetrahydrofuran, slowly add 2 g of 5-amino-2-fluorobenzoate and 0.5 mL of triethylamine under a nitrogen atmosphere, stir at 0 ° C for 60 min, stir at room temperature for 6 h, filter the product, wash it 3 times with 0.1 mol / L sodium bicarbonate solution, wash it 4 times with deionized water, wash it 2 times with anhydrous ethanol, each time for 15 min, and vacuum dry it at 70 ° C for 10 h to obtain modified carbon fiber;

[0075] (4) Take 800g of PVC resin, 300g of nitrile rubber powder, 200g of polyolefin thermoplastic elastomer, 100g of trioctyl trimellitate, 50g of dioctyl sebacate, 50g of aluminum hydroxide, 80g of carbon black, 100g of modified carbon fiber, 30g of heat stabilizer, 10g of antioxidant, and 10g of lubricant, and mix them evenly at 80°C with high-speed stirring, wherein the modified carbon fiber is added in equal amounts three times during the stirring process. The mixture is added to an internal mixer and kneaded at 165°C for 10 minutes to obtain a clinker, which is placed in a twin-screw extruder and extruded and granulated at 190°C to obtain a masterbatch, which is extruded through a screw extruder to obtain the outer sheath.

[0076] Comparative Example 1

[0077] A method for preparing a highly flexible and resistant robot cable outer sheath material comprises the following steps:

[0078] (1) Immerse 10 g of carbon fiber in 250 mL of ethanol / water mixture (volume ratio of ethanol to water is 95:5), add 1 g of KH570, adjust the solution pH to 4.5, stir at room temperature for 45 min, heat to 80 °C for reaction for 2 h, filter the product, wash it 4 times with 95 wt% ethanol solution, each time for 15 min, and dry it to obtain pretreated carbon fiber;

[0079] (2) Add 10 g of pretreated carbon fiber to 250 mL of anhydrous toluene, slowly add 10 mL of dimethylchlorosilane and 0.5 mL of Speier's catalyst solution (2 wt% H2PtCl6 isopropanol solution) under nitrogen atmosphere, stir at room temperature for 45 min, heat to 80 °C and reflux for 4 h, filter the product, wash with dry toluene 4 times, 15 min each time, and vacuum dry at 50 °C for 5 h to obtain an intermediate;

[0080] (3) Take 1000g of PVC resin, 600g of nitrile rubber powder, 300g of polyolefin thermoplastic elastomer, 300g of trioctyl trimellitate, 150g of dioctyl sebacate, 250g of aluminum hydroxide, 150g of carbon black, 200g of intermediate, 60g of heat stabilizer, 30g of antioxidant, and 30g of lubricant, and mix them evenly at 80°C with high-speed stirring, wherein the modified carbon fiber is added in equal amounts three times during the stirring process, and the mixture is added to an internal mixer, and internally kneaded at 165°C for 10 minutes to obtain a clinker, which is placed in a twin-screw extruder, extruded and granulated at 190°C to obtain a masterbatch, and the wire is extruded through the screw extruder to obtain the outer sheath.

[0081] Comparative Example 2

[0082] A method for preparing a highly flexible and resistant robot cable outer sheath material comprises the following steps:

[0083] (1) Immerse 10 g of carbon fiber in 250 mL of ethanol / water mixture (volume ratio of ethanol to water is 95:5), add 1 g of KH570, adjust the solution pH to 4.5, stir at room temperature for 45 min, heat to 80 °C for reaction for 2 h, filter the product, wash it 4 times with 95 wt% ethanol solution, each time for 15 min, and dry it to obtain pretreated carbon fiber;

[0084] (2) Take 1000g of PVC resin, 600g of nitrile rubber powder, 300g of polyolefin thermoplastic elastomer, 300g of trioctyl trimellitate, 150g of dioctyl sebacate, 250g of aluminum hydroxide, 150g of carbon black, 200g of pretreated carbon fiber, 60g of heat stabilizer, 30g of antioxidant, and 30g of lubricant, and mix them evenly at 80°C with high-speed stirring, wherein the modified carbon fiber is added in equal amounts three times during the stirring process, and the mixture is added to an internal mixer, and internally kneaded at 165°C for 10 minutes to obtain a clinker, which is placed in a twin-screw extruder, extruded and granulated at 190°C to obtain a masterbatch, and the wire is extruded through a screw extruder to obtain the outer sheath.

[0085] The sheath materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were tabletted to prepare test specimens that met the specifications. The tensile strength was tested with reference to GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets" to determine the mechanical properties of the samples; the flexural strength was tested with reference to GB / T 9341-2008 "Determination of flexural properties of plastics" to determine the flexural strength and determine the toughness of the samples; the impact strength of the samples was tested with reference to GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test"; the mass wear of the samples was tested with reference to GB / T 3960-2016 "Test method for sliding friction and wear of plastics"; the vertical burning grade of the samples was tested with reference to GB / T 2408-2021 "Determination of combustion properties of plastics - horizontal and vertical methods"; the limiting oxygen index of the samples was tested with reference to GB / T 2406.2-2009 "Determination of combustion behavior of plastics - oxygen index method - Part 2: Room temperature test"; the limiting oxygen index of the samples was tested with reference to ISO 1817-2015 Test sample oil resistance, the sample is a cylinder with a diameter of 16mm and a thickness of 4mm, immersed in 100℃ 20# engine oil for 100h, and the volume change rate is recorded; specific data are shown in Table 1.

[0086] Table 1 Test results of outer sheath material performance

[0087]

[0088] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A highly flexible and resistant bending robot cable, comprising a plurality of cable cores, wherein the plurality of cable cores are coated with a tape layer, wherein the twisted gaps of the cable cores are filled with a filler, wherein the tape layer is coated with a shielding layer, and the shielding layer is coated with an outer sheath layer; characterized in that: The outer sheath layer is made of the following components in parts by weight: 80-100 parts of PVC resin, 30-60 parts of nitrile rubber powder, 20-30 parts of polyolefin thermoplastic elastomer, 10-30 parts of trioctyl trimellitate, 5-15 parts of dioctyl sebacate, 5-25 parts of aluminum hydroxide, 8-15 parts of carbon black, 10-20 parts of modified carbon fiber, 3-6 parts of heat stabilizer, 1-3 parts of antioxidant, and 1-3 parts of lubricant; The method for preparing the modified carbon fiber comprises the following steps: (1) Immersing the carbon fiber in an ethanol / water mixture, adding KH570, adjusting the pH of the solution, stirring at room temperature, heating the solution for reaction, filtering, washing, and drying the product to obtain a pretreated carbon fiber; (2) adding the pretreated carbon fiber into anhydrous toluene, slowly adding dimethylchlorosilane and Speier's catalyst solution under a nitrogen atmosphere, stirring at room temperature, heating to reflux for reaction, filtering, washing, and drying the product to obtain an intermediate; (3) adding the intermediate to anhydrous tetrahydrofuran, slowly adding 5-amino-2-fluorobenzoate and triethylamine under a nitrogen atmosphere, mixing evenly at low temperature, stirring to react, filtering, washing, and drying the product to obtain a modified carbon fiber; Speier's catalyst solution is a 2 wt% H2PtCl6 solution in isopropanol.

2. The highly flexible and resistant bending robot cable according to claim 1, characterized in that: In step (1), the volume ratio of ethanol to water in the ethanol / water mixture is 95-99:5-1; the amount ratio of carbon fiber, ethanol / water mixture, and KH570 is 10 g: 200-300 mL: 0.1-1 g.

3. The highly flexible and resistant bending robot cable according to claim 1, characterized in that: In step (1), the pH is adjusted to 3.5-5.5, and the mixture is stirred at room temperature for 30-60 min. The temperature is raised to 60-80° C. for 2-4 h. The mixture is washed with 95 wt % ethanol solution for 3-5 times, each time for 15-20 min.

4. The highly flexible and resistant bending robot cable according to claim 1, characterized in that: In step (2), the usage ratio of the pretreated carbon fiber, anhydrous toluene, dimethylchlorosilane, and Speier's catalyst solution is 10 g: 200-300 mL: 5-10 mL: 0.1-0.5 mL.

5. The highly flexible and resistant bending robot cable according to claim 1, characterized in that: In step (2), stirring at room temperature for 30 to 60 minutes, the reflux reaction conditions are heating to 60 to 80°C and reflux reaction for 4 to 8 hours; washing with dry toluene 3 to 5 times, each time for 15 to 20 minutes; Vacuum dry at 40~60℃ for 4~6h.

6. The highly flexible and resistant bending robot cable according to claim 1, characterized in that: In step (3), the usage ratio of the intermediate, anhydrous tetrahydrofuran, 5-amino-2-fluorobenzoate, and triethylamine is 10 g: 200-300 mL: 2-5 g: 0.5-3 mL.

7. The highly flexible and resistant bending robot cable according to claim 1, characterized in that: In step (3), the low-temperature mixing condition is stirring at 0-5°C for 30-60 minutes; and the stirring reaction condition is reacting at room temperature for 6-12 hours.

8. The highly flexible and resistant to bending robot cable according to claim 1, characterized in that: The preparation method of the outer sheath layer comprises the following steps: mixing the raw materials uniformly at a high speed at 70-90° C. according to a proportion, wherein the modified carbon fiber is added in equal amounts three times during the mixing process, the mixture is added to an internal mixer, and internally kneaded at 160-175° C. for 8-12 minutes to obtain a clinker, which is placed in a twin-screw extruder, extruded and granulated at 180-200° C. to obtain a masterbatch, and extruded through a screw extruder to obtain the outer sheath layer.

9. A method for preparing a highly flexible and resistant bending robot cable as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: twisting a plurality of cable cores, adding fillers during the twisting process, extruding a tape layer outside the cable core, then weaving a shielding layer outside the tape layer, and finally extruding an outer sheath layer on the periphery, cooling, shaping, winding and packaging the finished cable to obtain the high-flexibility and bending-resistant robot cable.

Citation Information

Patent Citations

  • Tear-resistant and wear-resistant cable sheath material

    CN117467203A

  • Low temperature impact resistant modified polyvinyl chloride cable material

    CN107090147A

  • Heat-resistant flame-retardant control cable

    CN112309621A